Still procrastinating the no-regrets guide to getting it done - Ferrari, Joseph R.; Safari eBooks (Hoboken, N.J. : Wiley, 2010)
"In this book, the author provides an understanding of why some people habitually, compulsively, and chronically delay the start or completion of tasks to the point that they become upset and worried about meeting the deadline. Many of the procrastination books currently available focus on time-management techniques, but Dr. Ferrari, a procrastination expert and media personality, believes these books just scratch the surface of the issue. In this book, he shares more than two decades of research on the causes and consequences of chronic procrastination"--Provided by publisher.
Foreword / Timothy A. Pychyl -- Introduction: Why do we procrastinate? -- Everyone procrastinates, but not everyone is a procrastinator --"I'm better under pressure": the arousal procrastinator myth -- Indecision: decisional procrastination -- Why self-regulation fails: how you're your own worst enemy -- Perfection is pure fiction -- Does technology make it easier to procrastinate? -- Why the time of day and the tasks that need to be done matter to procrastinators -- The three R's of procrastination: reactance, revenge, and regret -- Social support: getting by with a little help from my friends -- Academic procrastination: why students delay, and how it affects the rest of their lives -- Procrastination at work -- Procrastination and personality styles -- Conclusion: Where do you go next-- and can you get there from here?
Description based on print version record.
Includes bibliographical references and index.
Keywords: Procrastination; Self-actualization (Psychology); Electronic books